Fatty acids, alkanones and alcohols from a major lower Triassic low-permeability petroleum reservoir - Cesar, Jaime; Robinson, Rachel; Naeher, Sebastian; Milovic, Marina; H. Ardakani, Omid (Frontiers in Earth Science, 2023)
For the first time, polar organic compounds in extracted bitumen from the Lower Triassic Montney Formation have been analyzed. This stratigraphic unit is one of the most prolific low-permeability reservoirs in Western Canada. However, its organic geochemical characterization is a challenge due to low biomarker concentration in the liquids and frequent mixing of gas/condensate hydrocarbons. Based on their contrasting molecular distributions, n-fatty acids and alkan-2-ones do not seem to share a common origin in these samples and do not have an apparent association with the n-alkanes. This study is also the first report of 1,13-, 1,14- and 1,15-diols in fossil organic matter; and in carbon number ranges of C15-C29, C16-C29 and C17-C29, respectively. The similar distributions of 1,14- and 1,15-diols suggests a common origin for these compound classes, whereas the 1,13-diols seem to derive from a different source or mechanism. A series of alkan-3-ols has also been identified in the C12-C28 range, sharing a common distribution pattern with the n-fatty acids. The large variability detected in the molecular distribution of oxygen-containing aliphatic compounds introduces the question whether they may record a geochemical signature that precedes thermal degradation and hydrocarbon migration events within Montney reservoirs.